Technical Performance of Grid-Connected Rooftop Solar PVs - Peter Asigri; Francis Boafo Effah; Daniel Opoku; Daniel Kwegyir; Anthony Kweku Eshun; Britney Asantewaa Owiredu; Mourad Bin Shafiyu; Sagoe De-Roy Ekow (International Journal of Energetica)
This paper presents a comprehensive analysis of the technical performance of grid-connected rooftop solar photovoltaic (PV) systems deployed in five locations along the solar belt of Ghana, namely Sakumono, Wa, Bolgatanga, Kumasi, and Kintampo. These locations were selected based on their diverse environmental conditions, offering a representative sample for the study. The study utilized PVSyst software version 7.3 to simulate the performance of the PV systems for each location, using south orientation, which gives the best results in the tilted global irradiation across all locations. According to the simulation results, the average performance ratio for the five locations was 79.7%, indicating the PV systems' highly efficient utilization of the available solar energy. The average final yield, representing the actual energy output, was also measured to be 4.38 kWh/kWp/day for the studied locations.  This study demonstrates the technical feasibility of Ghana's grid-connected rooftop solar PV installations. The results underscore the significance of optimal system design and orientation, emphasizing the potential for substantial renewable energy generation. The insights obtained from this study can aid policymakers, investors, and solar energy stakeholders in making informed decisions to promote the widespread adoption of rooftop solar PV systems in the region.